Injection drug use, unsafe medical injections, and HIV in Africa: a systematic review - Reid Savanna R (BMC, 2009)
Abstract The reuse of injecting equipment in clinical settings is well documented in Africa and appears to play a substantial role in generalized HIV epidemics. The U.S. and the WHO have begun to support large scale injection safety interventions, increased professional education and training programs, and the development and wider dissemination of infection control guidelines. Several African governments have also taken steps to control injecting equipment, including banning syringes that can be reused. However injection drug use (IDU), of heroin and stimulants, is a growing risk factor for acquiring HIV in the region. IDU is increasingly common among young adults in sub-Saharan Africa and is associated with high risk sex, thus linking IDU to the already well established and concentrated generalized HIV epidemics in the region. Demand reduction programs based on effective substance use education and drug treatment services are very limited, and imprisonment is more common than access to drug treatment services. Drug policies are still very punitive and there is widespread misunderstanding of and hostility to harm reduction programs e.g. needle exchange programs are almost non-existent in the region. Among injection drug users and among drug treatment patients in Africa, knowledge that needle sharing and syringe reuse transmit HIV is still very limited, in contrast with the more successfully instilled knowledge that HIV is transmitted sexually. These new injection risks will take on increased epidemiological significance over the coming decade and will require much more attention by African nations to the range of effective harm reduction tools now available in Europe, Asia, and North America.